Qing-Kai-Ling oral liquid alleviated pneumonia via regulation of intestinal flora and metabolites in rats - Chen, Hongying; Li, Siju; Pan, Biyan; Liu, Kun; Yu, Hansheng; Ma, Chong; Qi, Huiyuan; Zhang, Yuefeng; Huang, Xinyi; Ouyang, Dongsheng; Xie, Zhiyong (Frontiers in Microbiology, 2023)
Background: Qing-Kai-Ling (QKL) oral liquid, evolving from a classical Chinese formula known as An-Gong-Niu-Huang pills, is a well-established treatment for pneumonia with its mechanism remaining muddled. Studies have shown that the regulation of both intestinal flora and host-microbiota co-metabolism may contribute to preventing and treating pneumonia. The study aimed to investigate the potential mechanism by which QKL alleviates pneumonia from the perspective of ‘microbiota-metabolites-host’ interaction. Methods: We evaluated the therapeutic effects of QKL on lipopolysaccharide (LPS)-induced pneumonia rats. To explore the protective mechanism of QKL treatment, a multi-omics analysis that included 16S rDNA sequencing for disclosing the key intestinal flora, the fecal metabolome to discover the differential metabolites, and whole transcriptome sequencing of lung tissue to obtain the differentially expressed genes was carried out. Then, a Spearman correlation was employed to investigate the association between the intestinal flora, the fecal metabolome and inflammation-related indices. Results: The study demonstrated that pneumonia symptoms were significantly attenuated in QKL-treated rats, including decreased TNF-α, NO levels and increased SOD level. Furthermore, QKL was effective in alleviating pneumonia and provided protection equivalent to that of the positive drug dexamethasone. Compared with the Model group, QKL treatment significantly increased the richness and αlpha diversity of intestinal flora, and restored multiple intestinal genera (e.g., Bifidobacterium, Ruminococcus_torques_group, Dorea, Mucispirillum and Staphylococcus) that were correlated with inflammation-related indices. Interestingly, the intestinal flora demonstrated a strong correlation with several metabolites impacted by QKL. Furthermore, metabolome and transcriptome analyses showed that enrichment of several host-microbiota co-metabolites (arachidonic acid, 8,11,14-eicosatrienoic acid, LysoPC (20:0/0:0), LysoPA (18:0e/0:0), cholic acid, 7-ketodeoxycholic acid and 12-ketodeoxycholic acid) levels and varying lung gene (Pla2g2a, Pla2g5, Alox12e, Cyp4a8, Ccl19 and Ccl21) expression were observed in the QKL group. Moreover, these metabolites and genes were involved in arachidonic acid metabolism and inflammation-related pathways. Conclusion: Our findings indicated that QKL could potentially modulate intestinal flora dysbiosis, improve host-microbiota co-metabolism dysregulation and regulate gene expression in the lungs, thereby mitigating LPS-induced pneumonia in rats. The study may provide new ideas for the clinical application and further development of QKL.